Using 360 Degree Feedback System to Complement the Malaysian Public Service Performance Appraisal System : An Exploratory Study on the Instruments of 360 Degree Feedback System in the National Institute of Public Administration (INTAN) - Mohamed Nasser, Abdul Razak (2004)
360-degree feedback is a appraisal tool designed to quantify the competencies and skills of fellow employees by tapping the collective experience of their superiors, subordinates, and peers. The Malaysian civil service has established and implemented performance appraisal system since 1992. Yet the system has been criticized because of several drawbacks namely rater bias and its reward system. Therefore, this study would like to benchmark at another innovative appraisal system to complement the existing performance appraisal called the 360 degree feedback system. This research will try to evaluate the effectiveness of its implementation in INTAN and if it could be proven that it could play a complementary role in improving the implementation of the performance appraisal system in INTAN. A total of 90 (71.4 per cent) INTAN officers (JZTSA, Grade 1,2 and 3) were rated by their 2 supervisors, 5 collei2gues, 13 subordinates and they themselves (n=605). A self-administered questionnaire consists of 45 observable performance behavior expectations item were grouped into 7 dimension, namely, managing the organization, managing self, managing resources, leadership, motivating people, developing people and teamwork. The 1 - 10 point Likert Scale was used ranging from 1 -poor to 10-excellent performance behavior. Frequency distribution of the responses of the raters and the mean, median and mode of seven variables were analysed by using the Microsoft Excel spreadsheets. The result showed overall mean scores of the entire seven dimension was 7.0, which means the overall ratees performance behavior expectations/competencies is good. The study also showed supervisors (mean score 6.7) and subordinates(mean score 6.3) rate lower than colleagues(mean score 7.0) and self rating(mean score 7.2). This showed that there is a lot of room the officers to further improve their performance behavior either with the help from the organization management or by self improvement. From the interview conducted indicated that many employees accept the mean score rating given by the ratees and committed to discuss and improve either by with the help of their supervisors or by self improvement. Finally, it is strongly suggested in this study that the Malaysian Public Sector should adopt the 360 degree feedback appraisal system to further improve their efficiency and effectiveness of Government’s delivery system.